Palmar-plantar erythrodysaesthesia during pegylated liposomal doxorubicin treatment – case report - Cybulska-Stopa, Bożena; Ziobro, Marek; Skoczek, Marta; Cedrych, Ida (Contemporary Oncology/Współczesna Onkologia, 2011)
Palmar-plantar erythrodysesthesia (PPE), also called hand-foot syndrome (HFS), is a distinctive and relatively frequent dermatological toxic reaction associated with certain chemotherapeutic agents: pegylated liposomal doxorubicin, capecitabine, a long-circulating formulation of doxorubicin, cytosine arabinoside, interleukin 2. HFS typically presents with dysaesthesia and tingling in the hands and feet. Dysaesthesias and erythema may occur on several other body surfaces, especially in areas where pressure or increased warmth occurs, such as on the buttocks, groin, under pendulous breasts, and in the axillae. We present the case of a 56-year-old woman with HFS in the axillae, inguen and on the skin of the back and abdomen during treatment with pegylated liposomal doxorubicin for metastatic breast cancer. After four cycles of chemotherapy, treatment was interrupted due to HFS (G3 according to NCI CTC). Palmar-plantar erythrodysaesthesia is an oppressive complication after chemotherapy; it often makes normal daily activity impossible, deteriorates the patient’s quality of life and frequently limits chances of effective treatment.